Vascular Biology Protocols - Sreejayan, Nair.; Ren, Jun.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2007)
Over the past decades, the pathogenesis, diagnosis, treatment and prevention of cardiovascular diseases have been benefited significantly from intensive research activities. In order to provide a comprehensive "manual" in a field that has become as broad and deep as cardiovascular medicine, Vascular Biology Protocols covers a wide spectrum of in vivo and in vitro techniques encompassing biochemical, pharmacological and molecular biology disciplines which are currently used to assess vascular disease progression. Each chapter included in this volume focuses on a specific vascular biology technique and describes various applications as well as caveats of these techniques. The protocols included here are described in detail, allowing beginners with little experience in the field of vascular biology to embark on new research projects. Comprehensive and easy-to-use, Vascular Biology Protocols will prove valuable for all those who wish to broaden their knowledge of cardiovascular research tools.
Rat Carotid Artery Balloon Injury Model -- Histological and Morphometric Analyses for Rat Carotid Balloon Injury Model -- Plaque Rupture Model in Mice -- Immunostaining of Mouse Atherosclerotic Lesions -- Surgical Animal Model of Ventricular Hypertrophy -- Animal Models of Hypertension -- Rat Models of Cardiac Insulin Resistance -- The Isolated, Perfused Pseudo-Working Heart Model -- Altering and Analyzing Glucose Metabolism in Perfused Hearts of Transgenic Mice -- Methods in the Evaluation of Cardiovascular Renin Angiotensin Aldosterone Activation and Oxidative Stress -- Detection and Quantification of Apoptosis in the Vasculature -- Endothelial Progenitor Cell and Mesenchymal Stem Cell Isolation, Characterization, Viral Transduction -- Assessment of Endothelial Damage/Dysfunction: A Focus on Circulating Endothelial Cells -- Evaluation of Endothelial Function by In Vivo Microscopy -- Haptotaxis of Endothelial Cell Migration Under Flow -- Isolation, Culture, and Functional Analysis of Adult Mouse Cardiomyocytes -- Mechanical Measurement of Contractile Function of Isolated Ventricular Myocytes -- Studying Ischemia and Reperfusion in Isolated Neonatal Rat Ventricular Myocytes Using Coverslip Hypoxia -- Isolation and Functional Studies of Rat Aortic Smooth Muscle Cells -- Detection of Reactive Oxygen Species and Nitric Oxide in Vascular Cells and Tissues -- Assessment of Protein Glycoxidation in Ventricular Tissues -- Assessment of PI-3 Kinase and Akt in Ischemic Heart Diseases in Diabetes -- Two-Dimensional Gel Electrophoresis in Platelet Proteomics Research -- Stem Cell Therapy in the Heart and Vasculature.
Keywords: Medicine; Molecular biology; Cardiology; Biomedicine; Molecular Medicine; Cardiology; Electronic books